Meningkan Hasil Belajar Bahasa Indonesia Pokok Bahasan Minat Baca Dengan Menggunakan Model Sosiodrama Siswa Kelas X MA Nurul Huda - M. Rosyid Ridlo; Ulya Nurul Laili (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The purpose of this writing is to determine the factors that influence reading interest and interest in class X MA Nurul Huda Lumajang students through the sociodrama method. This type of research is qualitative research with a descriptive approach. Class X students are the subjects. The influencing factors are internal and external factors. Internal factors include intelligence, interest and attention, motivation, perseverance, attitude, reading habits, as well as physical fitness and health. Students will not be interested in reading if they do not have the desire, health, physical fitness, intelligence and motivation. Bad libraries, outdated reading materials, some even unused, little encouragement from teachers, no encouragement from parents, parents who do not provide encouragement due to lack of funds, no parental attention to children's reading. Most parents focus more on learning outcomes, reading habits that students have not acquired since childhood. The influence of the reading environment and playmates indirectly influences students' interest in reading. The uncontrolled influence of technology. For example, the influence of misuse of smartphones or gadgets, the influence of television programs on students who forget their student responsibilities.